Komplikasi pada Pasien Fraktur Klavikula Pasca Penatalaksanaan Operatif di RS Bina Sehat Jember periode 2007-2012 - Adhitya Wicaksono; Muhammad Hasan; Irawan Fajar Kusuma (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
The prevalence of clavicle fracture is 5 % out of all fractrues. The most common cause of clavicle fracture is shoulder trauma due to an accident because of a fall or a traffic accident, but sometime non traumatic factor can cause clavicle fracture. Management of clavicle fracture is operative or non-operative treatment, both has a possible complications. The study aimed to find out the complication of clavicle fracture after operative treatment, compared to its contralateral. This was an analytical survey study, using saturated sampling system. There were 16 samples according to the inclusion criteria. The result revealed that a comparison of the ROM value, muscle strength, shortened-bone, and muscle atrophy were p>0.05 meaning no significant difference between 2 groups. A compariosn of NRS value, touch sensation, and deformity were p<0.05 meaning there is a significant difference between 2 groups. It can be concluded that in post clavicle fracture patient treated with operative therapy there was no complication on shoulder joint ROM, shoulder muscle strength, shortened-bone, and muscle atrophy, but a complication can be found on NRS clinical examination, touch sensation and deformity. Keywords: clavicle fracture, operative, complications.